Confirmatory Factor Analisys (CFA) untuk Validasi Instrumen Percieved External Prestige di Lingkungan Kerja - Salu, Lorena Tiku; Umasugi, Muhammad Irwan; Triputra, Gusti Razuli; Randa, Andreas Galileo; Ardiansyah, Fuad (Universitas Muhammadiyah Metro, 2025)
Perceived External Prestige (PEP) is an individual's assessment of how their organization is viewed by outsiders. This study aims to validate the Perceived External Prestige (PEP) instrument as a measurement tool for employee perceptions of organizational reputation in the eyes of external parties. Validation was conducted using Confirmatory Factor Analysis (CFA) method on a sample of 251 private employees in Southwest Papua. The three-factor model of PEP tested includes Personality, Social Development, and Career Training. The analysis results show that the model has a good fit with the empirical data. A high Kaiser-Meyer-Olkin (KMO) value of 0.963, and a significant Bartlett's test (p < 0.05) indicated that the data were suitable for further factor analysis. All items in the instrument had factor loadings above the 0.35 threshold, indicating good construct validity. These validation results confirm that the PEP instrument is effective and reliable for measuring employee perceptions of organizational reputation in the work environment. This research contributes to the development of a valid and reliable instrument to measure PEP in the context of organizations in Indonesia.